A critical review with emphasis on the rheological behavior and properties of polymer solutions and their role in membrane formation, morphology, and performance - Mousavi, Seyedeh Mohaddeseh; Raveshiyan, Saba; Amini, Younes; Zadhoush, Ali (Advances in colloid and interface science, 2023)
Considering the importance of asymmetric membrane morphology in controlling the performance of various membrane systems as well as the rapid development of membrane technologies in different industries, the control of membrane manufacturing processes and effective parameters is considered an outstanding subject. Therefore, it seems that investigating the rheological properties of polymer solutions, including gelation behavior, viscoelasticity, and their effect on membrane formation, as well as the morphological structure of membranes, such as hollow fiber and flat sheet membranes, is a requirement for the production of asymmetric membranes with desirable properties. One of the most widely used techniques for the preparation of asymmetric membranes is phase separation. Its two main mechanisms are liquid-liquid demixing and solid-liquid demixing, which can affect the morphology of the membranes in the membrane formation process. Therefore, the membrane morphology can be greatly influenced by controlling the phase separation in the early stages. In this study, an attempt has been made to investigate the rheological behavior of polymer solutions and other factors during the membrane fabrication process, affecting the morphological structure of membranes. The principles governing the rheology of polymer solutions, such as shear, elongation, viscosity, and viscoelasticity have a vital role in determining the membrane morphology and separation performance. Due to the interaction of the rheology of polymer solutions and phase separation, the effects of changes in the rheological properties of the phase separation and the formation of membranes with different structures and morphologies are studied. Furthermore, in addition to the analysis of the effect of the relaxation time and gelation mechanisms, discussions are provided for the determination of the final membrane morphology considering the competition between the domain growth and gelation rates. Finally, the effect of controlling the rheological behavior and phase separation on the membrane structure and performance was investigated in several membrane applications. (1)Membrane with dense structure (vitrification boundary).(2)Porous membrane from nucleation and growth of polymer-poor phase.(3)Membrane with bi-continuous (lacy) structure from spinodal decomposition.(4)Porous membrane from nucleation and growth of polymer-rich phase. [Display omitted] •Influence of principles governing the rheology of polymer solutions on the membrane morphology and separation performance.•The competition between growing regions and gelation rate has a great impact on the final membrane morphology.•Controlling the rheological behavior and phase separation in the membrane fabrication affects the morphology and performance.